Agro-hydrological modeling systems in Peninsula Malaysia: panacea to youth development - Zakari, Muazu Dantala; Rowshon, Md. Kamal; Mohamed Ramli, Norulhuda; Mohamed Rehan, Balqis (Human Resource Management Academic Research Society, 2024)
This paper considers the role of Agro-Hydrological Modeling Systems (AHMS) in fostering youth progress in Peninsula Malaysia. In the face of rising world challenges, climate change, increase in population, and resource scarcity, the sustainable management of agriculture and water resources is supreme. Peninsula Malaysia, renowned for its rich agricultural diversity, serves as a unique backdrop at the crossroads of various challenges, offering an ideal context to explore the potential of AHMS in youth empowerment. This study is exploratory, using data gathered from documents and literature analyses. This paper not only underscores the significance of AHMS in the Malaysian context but also elucidates its concrete impact on fostering youth engagement, education, innovation, and the cultivation of sustainable farming practices. Furthermore, it observes the obstacles encountered in implementing AHMS for youth development, highlighting the various opportunities awaiting exploration.